1978
DOI: 10.1136/oem.35.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Byssinosis, respiratory symptoms and spirometric lung function tests in Tanzanian sisal workers

Abstract: Byssinosis and other respiratory symptoms and acute and chronic changes in FVC and FEVy.o were investigated in 77 workers in sisal spinning and 83 workers in sisal brushing departments in six Tanzanian sisal factories. Although the prevalence of byssinosis in spinning departments was found to be low (5.2 %), it was very high in brushing departments (48.2 %). Workers in brushing were exposed to sisal dust for a significantly longer period (I177 + 7.3 years) compared to workers exposed to sisal in spinning (2-85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
4
22
1
Order By: Relevance
“…The across-shift reductions were similar in women and men and varied from 0.6-4.0% for FVC, from 1.0-4.9% for FEV,, from 1.7-9.1% for FEFsO and from 2.3433% for FEF,,. The magnitude of these reductions was similar to the across-shift changes seen in cotton, jute, and sisal workers Ghawabi, 1978;Mustafa et al, 1978;Velvart, 19721, but was less than those seen with hemp or flax workers Zuskin, 1971, 1972;Zuskin et al, 19901. Such across-shift declines in otherwise healthy workers suggest an acute irritative effect of wool dust in airways since normal diurnal variation is associated with daytime improvement in lung function.…”
Section: Discussionsupporting
confidence: 54%
“…The across-shift reductions were similar in women and men and varied from 0.6-4.0% for FVC, from 1.0-4.9% for FEV,, from 1.7-9.1% for FEFsO and from 2.3433% for FEF,,. The magnitude of these reductions was similar to the across-shift changes seen in cotton, jute, and sisal workers Ghawabi, 1978;Mustafa et al, 1978;Velvart, 19721, but was less than those seen with hemp or flax workers Zuskin, 1971, 1972;Zuskin et al, 19901. Such across-shift declines in otherwise healthy workers suggest an acute irritative effect of wool dust in airways since normal diurnal variation is associated with daytime improvement in lung function.…”
Section: Discussionsupporting
confidence: 54%
“…This is in agreement with a study in Croatia [10]. In our study, workers in the brushing departments had the highest prevalence of acute symptoms which is in agreement with the findings of Mustafa et al [7]. Low prevalence of byssinosis which is considered to be among chronic obstructive respiratory diseases was found in two other studies among sisal workers, but these also reported low dust levels [5,6].…”
Section: Discussionsupporting
confidence: 83%
“…The demand for sisal is increasing due to increased awareness of the benefits of natural fibres, development of new sisal products and power generation [3,4]. Little is known on respiratory effects among sisal workers, but a few studies have shown higher prevalence of respiratory symptoms among these workers [5][6][7]. No recent studies have been performed among sisal workers in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of air pollution in the occurrence of COPD remains to be demonstrated [5]. In Africa, most prevalence studies of COPD have been conducted on specific groups of the population: miners, farmers or workers in industrial areas and also in hospital patients [38]- [43]. The prevalence of chronic bronchitis among no-exposed workers varied between 3.5% and 17% [39] [40] [41] and was always higher among exposed workers (4.1% to 38.5%) [38]- [43].…”
Section: Epidemiology Of Air Pollution Related To Traffic and Copd Inmentioning
confidence: 99%
“…In Africa, most prevalence studies of COPD have been conducted on specific groups of the population: miners, farmers or workers in industrial areas and also in hospital patients [38]- [43]. The prevalence of chronic bronchitis among no-exposed workers varied between 3.5% and 17% [39] [40] [41] and was always higher among exposed workers (4.1% to 38.5%) [38]- [43]. In Africa, the proportion of patients with COPD varies from country to country, from 2.7% in pneumology services in Conakry to 14% in specialized hospitals in pneumology in Morocco [27] [48].…”
Section: Epidemiology Of Air Pollution Related To Traffic and Copd Inmentioning
confidence: 99%